Factors Affecting Dynamic Archive Management in General and Academic Sub Division in University of Brawijaya - Sovia Rosalin (Jurnal VOK@SINDO, 2016)
This study aims to determine the factors that influence the management of records in the general and academic sub-divisions in University of Brawijaya This research is a descriptive study using a qualitative approach. Informants in the study are the Head of the general and / or academic sub-divisions in Vocational Education, Faculty of Medicine, Faculty of Engineering, Faculty of Humanities, Faculty of Animal Science, Faculty of Social and Political Sciences, Faculty of Agriculture, Faculty of Mathematics and Natural Sciences, Faculty of Agricultural Technology, Faculty of Computer Science, Faculty of Administrative Sciences and Faculty of Fisheries and Marine Science. Instrument used are observation sheet, interview guide and questionnaire. The findings show that factors influencing the management of records in UB include lack of budget to support archival unit: working environment archival that include temperature, humidity, lighting; availability of the archive room; lack of employees majoring in archive; unavailability of SOP regarding record keeping in the Faculty of Brawijaya University; inadequate facilitie; and not standardized recording system. Regarding this, the faculties in University of Brawijaya, including Vocational Education Program, are suggested to have better record management for dynamic archives in the general and academic sub-division.